Caricature-based antenatal breastfeeding education trial: A randomized controlled trial - Fouzia Abdulaziz Alhreashy; Arwa Abdulelah Mobeirek; Osama Abdulelah Mobeirek; Salem Dakheel Al-Suwaidan; Nawal Mohammed AlRajeh; Monirh Abdulaziz Alhorishi (Wolters Kluwer Medknow Publications, 2024)
Objectives: Cartoons, comics, and caricatures have been incorporated in health education. This trial aimed to evaluate the effectiveness of caricature-based breastfeeding education at improving breastfeeding knowledge, attitudes, self-efficacy, and practice among pregnant women. Materials and Methods: A randomized controlled clinical trial was carried out at Riyadh First Health Cluster in Saudi Arabia. A total of 85 pregnant women were randomly assigned to the intervention group (n = 41) or the control group (n = 44). The intervention was two caricature-based versus one standard online lecture in breastfeeding. The participants were followed up for 3 months postpartum. The primary outcome was full breastfeeding (predominant and exclusive breastfeeding) by the time infants were 3 months old. The secondary outcomes were prenatal and postnatal breastfeeding self-efficacy, Iowa Infant Feeding Attitude Scale (IIFAS) scores, and satisfaction with the education. Results: The participants were mostly Saudi (97.6% vs. 90.9%) and housewives (79% vs. 86.4%) for the intervention and control groups, respectively. The full breastfeeding rate at 3 months postpartum was 32.5% for the intervention and 31.6% for the control (P = 0.808; 95% confidence interval 0.539-1.965; relative risk = 1.029). Prenatal breastfeeding, postnatal self-efficacy, and IIFAS scores were compared between the intervention and control groups; no statistically significant difference was found (P > 0.05). In both arms of the study, participants' experiences with the health education were satisfactory. Conclusion: Caricature use in antenatal breastfeeding education was a pleasant experience, but its effect on self-efficacy, attitudes, and behavior could not be determined from this trial. Large-scale, multi-center, multi-component research is recommended.